Teacher RePlay and Children ReAct: pilot testing a formative toolkit to support playful learning in the classroom - Omoeva, Carina; Zosh, Jennifer M.; Pyle, Angela; D'Sa, Nikhit; Contreras Gomez, Rafael; Dooley, Brian; Giacomazzi, Mauro; Ariapa, Martin; Maldonado-Carreño, Carolina; Escallón, Eduardo; Dey, Gopal; Pavel, Kazi Ferdous; et al. (Frontiers in Education, 2024)
Playful learning has seen a resurgence of interest in the past decade, particularly in contexts where play is not traditionally part of a teacher's repertoire. Teachers interested in exploring the integration of play in their classrooms need formative tools and resources that help them to reflect and assess their own practice and their ability to create a playful learning experience for their students. This study presents the results of two rounds of pilot testing in three countries for Teacher RePlay, a new open-source toolkit designed to support teachers interested in reflecting on and deepening their learning through play practice. The toolkit includes the main Teacher RePlay observation protocol for teachers, as well as Children ReAct, a complementary protocol for a photo-elicited focus group discussion with children, intended to directly assess children's experiences and reflections on learning through play. Upon observation, teachers receive customized coaching suggestions and tips designed to strengthen their learning through play practice. Initial results from the piloting indicate that the toolkit holds strong potential for teachers interested in better understanding and deepening their playful learning practice. This paper discusses the development, validation, successes, and challenges of the Teacher RePlay toolkit, and identifies future directions for its use.